PERSEPSI TAMU TENTANG KUALITAS PELAYANAN PADA DEPARTEMENT TATA GRAHA DI HOTEL IBIS PADANG - Yulianti Yulianti; Ira Meirina Chair; Hijriyantomi Suyuthie (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
The research purpose is to know perception about the service quality at the hotel’s housekeeping department Ibis Padang. Research type is Quantitative descriptive, this population are visitors at the Hotel Ibis Padang. Population of this research are about 5036 people. The study sample selection teacnique uses incidential sampling with a sample of 100 people. The data collecting are by questioner with likert scale which has proven validistas and realibilitas. This study consists of five indicators of service quality, namely: reliability, responsiveness, assurance, empathy, and tangibles. The study concluded that the general perception about the quality service of a housekeeping department at the Hotel Ibis Padang expressed good with 78% of responden. Keywords : Perception, Quality Service.